Technical Assistance in Developing the SELANTANG Standard 3 Handbook to Foster Older Adult Ambassadors in Medan City - Hodriani Hodriani; Nurmala Berutu; Rahmulyani Rahmulyani; Marsal Risfandi; Rahayu Lubis; Junaidi Junaidi; Ni Kadek Suwardani (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
The increasing elderly population necessitates the strengthening of empowerment programs that support the development of active, healthy, and independent older adults. However, the Sekolah Lansia Mandiri (Independent Elderly School) still faces limitations in learning guidelines and facilitator capacity to achieve Standard 3. Therefore, this community service program aimed to integrate the SELANTANG Standard 3 concept through the development of a learning guidebook and the enhancement of the capacities of cadres and facilitators to promote older adults as Elderly Ambassadors (Duta Lansia). The method employed was Participatory Action Research (PAR), consisting of needs assessment, curriculum development and preparation of the SELANTANG Standard 3 Book, mentoring of cadres and facilitators, learning implementation, and collaborative evaluation and reflection. The program involved approximately 70 participants, including older adults, Bina Keluarga Lansia (BKL) cadres, facilitators, and relevant stakeholders. Meanwhile, the effectiveness evaluation was conducted on 20 participants who completed the entire mentoring program. The results demonstrated that the SELANTANG Standard 3 Book was successfully developed and implemented as a learning guide to support the establishment of Elderly Ambassadors. Evaluation findings indicated an improvement in participants’ understanding, as reflected by an increase in the mean score from 42.5 in the pretest to 80.5 in the posttest, representing a gain of 38 points. The Paired Sample t-Test analysis revealed a statistically significant difference between the pretest and posttest scores (p < 0.05). In addition, the mentoring program enhanced the readiness of cadres and facilitators to manage learning activities in a more structured, participatory, and sustainable manner. These findings suggest that the SELANTANG Standard 3 Book has the potential to serve as an effective learning guide in strengthening the capacity of Sekolah Lansia Mandiri and supporting the development of Elderly Ambassadors in Medan City.